1993
DOI: 10.1037/0022-3514.64.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Delayed costs of suppressed pain.

Abstract: The study demonstrates that the rebound effect of thought suppression (Wegner, 1989) has an analog in the experience of somatic discomfort. During a cold-pressor pain induction, 63 Ss were instructed either to concentrate on their room at home (distraction), to pay close attention to their hand sensations (monitoring), or to remove awareness of those sensations from mind (suppression). Two min of postpressor pain ratings showed that monitoring produced the most rapid recovery from the pain and that suppression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
199
3
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(220 citation statements)
references
References 40 publications
15
199
3
3
Order By: Relevance
“…A pervasive tendency to avoid thus seems to be associated with more, rather than less distress. This is indeed in line with the experimental research that has shown that attempts to avoid and control unwanted private events not only were largely ineffective, but have also been found to result in the occurrence of more, rather than less unwanted private events (Purdon, 1999;Cioffi & Holloway, 1993). Attempts to control anxiety in the face of ongoing stress have been shown to exacerbate physiological arousal (Wegner, 1994).…”
Section: The Centrality Of Avoidancesupporting
confidence: 68%
“…A pervasive tendency to avoid thus seems to be associated with more, rather than less distress. This is indeed in line with the experimental research that has shown that attempts to avoid and control unwanted private events not only were largely ineffective, but have also been found to result in the occurrence of more, rather than less unwanted private events (Purdon, 1999;Cioffi & Holloway, 1993). Attempts to control anxiety in the face of ongoing stress have been shown to exacerbate physiological arousal (Wegner, 1994).…”
Section: The Centrality Of Avoidancesupporting
confidence: 68%
“…In addition, their results support the findings of recent studies that control strategies such as avoidance, substitution, elimination, etc., of uncomfortable private events (i.e., thoughts, emotions, bodily sensations, etc.) may actually increase the intensity, frequency, duration, or even accessibility of the unwanted sensations, thereby generating further problems and suffering (e.g., Campbell, Barlow, Brown, & Hoffman, 2006;Cioffi & Holloway, 1993;Gross & Levenson, 1997;Gutiérrez, Luciano, Rodríguez, & Fink, 2004;Webner & Erber, 1992; see reviews by Purdon, 1999;Rassin, Merckelbach, & Muris, 2000; and a meta-analysis by Abramowitz, Tolin & Street, 2001).…”
mentioning
confidence: 99%
“…In a similar study, subjects who were told to pay close attention to their hand during a cold-pressor task recovered more quickly and were less likely to rate a second task as unpleasant than those who were told to either distract themselves or suppress the sensation (Cioffi & Holloway, 1993). Thus, in addition to preliminary evidence that acceptance-based behavior therapies are promising treatments as a whole, there is evidence of specific effects on measures of acceptance (Bond & Bunce, 2000;Cordova et al, 1998) and when compared to control strategies, acceptance strategies promote greater tolerance and quicker recovery from painful experiences (Cioffi & Holloway, 1993;Hayes, Bissett, et al, 1999).…”
Section: Empirical Evidencementioning
confidence: 97%